2020
DOI: 10.1093/mnras/staa4002
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of coronal mass ejections on cosmic-ray intensity modulation with algorithm selected Forbush decreases

Abstract: The relationship between coronal mass ejections (CMEs) and Forbush decreases (FDs) has been investigated in the past. But the selection of both solar events are difficult. Researchers have developed manual and automated methods in efforts to identify CMEs as well as FDs. While scientists investigating CMEs have made significant advancement, leading to several CME catalogues, including manual and automated events catalogues, those analyzing FDs have recorded relatively less progress. Till date, there are no com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…The FD-SWS correlation r=0.44 obtained in the present investigation is in agreement with their result. Our results for FD-SWS (r=0.44) and FD-IMF (r=0.44) do not reflect the submission of Okike et al (2021b) who obtained r=0.81 and ∼ 0.34 respectively. This could be a result of the data periods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The FD-SWS correlation r=0.44 obtained in the present investigation is in agreement with their result. Our results for FD-SWS (r=0.44) and FD-IMF (r=0.44) do not reflect the submission of Okike et al (2021b) who obtained r=0.81 and ∼ 0.34 respectively. This could be a result of the data periods.…”
Section: Discussioncontrasting
confidence: 99%
“…Investigations on the remaining FD data in Table 2 will be taken up in future work. FDs with (CR(%) ≤ −3) are often adopted as the common threshold to select large FDs (e.g., Kristjánsson et al 2008;Kane 2010;Okike et al 2021b). The matrix of correlation results for large FDs with corresponding solar wind and geomagnetic activity index data is given in Table 1.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Kilpua et al (2017) investigated 300 ICMEs and found that 80% of them were associated with Forbush Decreases (FDs), and proposed that the acceleration effect by the ICMEs led to a 20%-25% decreases of CRI as observed by both ground-based neutron monitors and space instruments. Okike et al (2021) also found that the FDs of CRI were closely related to ICMEs.…”
mentioning
confidence: 81%
“…Harrison et al (2011) indicate the need to remove effect of solar cycle variations from CR data before FD event selection. Third, CR anisotropy, known to exert significant influence on the number, magnitude, and timing of Forbush events (Pomerantz & Duggal, 1971;Belov, 2008;Okike et al, 2021b) was not accounted for in the current work.…”
Section: • Bayesian Blocks Algorithmmentioning
confidence: 92%
“…Besides the versions of our Fourier-R-based FD location algorithm which has be used in various applications such as Okike & Umahi (2019b), Okike (2019b), Okike & Umahi (2019a), Okike (2020) and Okike et al (2021b), we know of no other publications that have fully automated Forbush event identification.…”
Section: Algorithm-based Identification Methodsmentioning
confidence: 99%